Trends in Motor Performance of First Graders: A Comparison of Cohorts from 2006 to 2015 - Spengler, Sarah; Rabel, Matthias; Kuritz, Arvid Marius; Mess, Filip (Frontiers in Pediatrics, 2017)
Background: Motor performance is an important factor for health. Already in childhood, motor performance is associated with e. g. obesity and risk factors for cardiovascular diseases. It is widely believed that the motor performance of children has declined over recent years. However, this belief is lacking clear evidence. The objective of this study was to examine trends in motor performance of first grade students during a period of ten years (2006-2015). We examined trends in (a) aerobic fitness, (b) strength, (c) speed and (d) balance for boys and girls separately and considered BMI as a potential confounder. Methods: From 2006 to 2015 we tested 5,001 first graders (50.8% boys; mean age 6.76 (0.56) years) of 18 primary schools in Germany. Each year between 441 and 552 students of the same schools were surveyed. Performance tests were taken from the Motorik-Module Study and the “German Motor Ability Test”: “6 minutes run”, “push-ups”, “20 meter sprint”, “static stand”. Linear regression models were conducted for statistical analysis. Results: A slightly negative trend in aerobic fitness performance was revealed in boys (ß = -0.050; p = 0.012) but not in girls. In the strength performance test no trend over time was detected. Performance in speed (boys: ß = -0.094; girls: ß = -0.143; p ≤0.001) and balance tests (boys: ß = -0.142; girls: ß = -0.232; p ≤0.001) increased over time for both boys and girls. These findings held true when BMI was considered. Conclusion: This study only partly supported the assumption that motor performance of children has declined: in our study, aerobic fitness declined (only in boys), while strength remained stable and speed and balance even increased in both sexes. Moreover, it seems as if BMI can explain changes in performance only to a small extent. Changed lifestyles might be a substantial cause. Further research on recent trends of motor performance and interacting variables is needed to support the results of our study and to provide more knowledge on causes of these trends.